Characterization Of White Spot Syndrome Virus (WSSV) From Indonesian Shrimp Farms And Development Of Polymerase Chain Reaction (PCR) Assay For Its Detection - Sunarto, Agus (2001)
A study was carried out to clarify the viral white spot disease in Indonesian shrimp farms and to develop a polymerase chain reaction (PCR) assay for its detection. Giant tiger shrimp (Penaeus monodon Fabricius) were collected from Indonesian shrimp farms that had a history of high mortality. The identification of shrimp infected with white spot was based on the clinical signs, particularly on the appearance of white spots on the cephalothorax and body shell. The shrimp was either preserved in Davidson's fixative, 4% glutaraldehyde or 70% ethanol and subsequently were used for histopathological study, ultrastructural analysis and DNA extraction, respectively. Clinical history of the diseased shrimp included reduced feed intake before dying which surged rapidly up to 100% within a week. The disease occurred in shrimp of all ages, regardless of stocking density and culture system. The pathognomonic clinical sign of white spots on the carapace developed from a tiny spot to 3mm in diameter to a hibiscus-like shape. Histopathological examination of the diseased shrimp revealed generalised tissue damage and cellular changes in subcuticular epidennis, gill, stomach, hematopoietic tissue, lymphoid organ, hepatopancreas, heart, nervous tissue and muscle. Marked eosinophilic to basophilic intranuclear Cowdry A-type inclusion bodies were observed in infected cells. Transmission electron microscopy observation of diseased shrimp continned the features of Cowdry Atype intranuclear inclusion body as seen under light microscope and the presence of virus particles in the intranuclear inclusion bodies in hypertrophied nuclei. The virus was a non-occluded, ovoid, trilaminar enveloped and measured 328±24 nm and 122±27 nm in length and width, respectively. The nucleocapsid was cylindrical, measured 253±30 in length and 80±7 nm in width with unique appearance of 14 to 17 striated structures. The core of the nucleocapsid was highly electron-densed and separated from the envelope by an electron-lucent layer. The virus morphogenesis took place in the nucleus with membranous labyrinth as its support system. The virus had four structural proteins namely 19, 23,27 and 75 kDa in size. Nested PCR assays developed using primers designed from WSSV-DNA sequence available in GenBank® (Thai and Korean isolates) and from published primers (Taiwanese and Japanese isolates) proved to be specific and sensitive for the detection of WSSV from Indonesian shrimp farms. However, the primer pairs constructed from highly conserved region of ribonuclease reductase gene from Thai isolate was the most sensitive PCR assay against WSSV. Based on the gross signs, histopathogical changes, ultrastructural observation and PCR results, it was confirmed that white spot disease occurred in Indonesian shrimp farms due to viral agent. Based on the viral ultrastructure, morphogenetic pathway and the genomic homology sequence, the virus was similar with WSSV previously reported in other Asian countries.